Telisik Faktor Pengaruh Kinerja Maqashid Syariah Bank Syariah Di Indonesia - Ardiani Ika Sulistyawati; Hanik Ati; Aprih Santoso (Jurnal Ilmiah Ekonomi Islam, 2020)
This study aims to examine the effect of temporary syirkah funds, board of commissioners, independent commissioner, sharia supervisory board, dual position of sharia supervisory board, audit committee, and audit committee meeting on maqasid syariah performance of Islamic bank in Indonesia during the period 2015 – 2017. The sample of this study was chosen by purposive sampling and obtained data 33 banks with 11 banks per year. This hypothesis testing in this study used multiple regression model. The result shows that temporary syirkah funds, board commissioners, sharia supervisory board, dual position of sharia supervisory board, and audit committee have an effect on maqasid syariah performance of Islamic bank. However, audit committee meeting do not have an effect on maqasid syariah performance of Islamic bank.